Assessment of Knowledge of Bio Medical Waste Management in Third and Final Year BDS Students - Ali, Akhtar; Qureshi, Anusha; Mahnoor, Syeda; Ahmad, Farah (Infectious Diseases Journal of Pakistan, 2022)
Background: Healthcare activities generate wastes of various quality and quantity. The waste varies from being hazardous to nonhazardous for the healthcare workers. The risk of infection amongst the medical personnel and staff, especially dental surgeons, increases with the inadequate management of the biomedical waste disposal. The data regarding proper biomedical waste disposal (BMW) is almost scarce across Pakistan. Methodology: Across-sectional study was conducted amongst the third year and final year dentistry students of Liaquat University of Medical and Health Sciences Jamshoro, to gauge their knowledge of proper waste disposal methods. A questionnaire-based Performa was prepared for the students. Total of 107 students participated in it. The data was recorded and analyzed using SPSS version 20. Chi-square test was applied to compare the data and p-value less than 0.05 was considered significant. Results: Out of 107 students, 56 were from third year and 51 from final year. It was found that majority of students in both years lacked knowledge if their college followed the BMW guidelines or not. Most of the students also lacked knowledge about the BMW segregation categories. Conclusion: Lack of knowledge in proper waste disposal among health care workers who are directly involved in generating and disposing medical waste is a serious concern. To overcome this challenge knowledge regarding BMW management should be part of the curriculum that needs to be taught and practiced at all levels of undergraduate education. Keywords: Biomedical waste, Knowledge, Attitude, BDS students